2019
DOI: 10.1115/1.4043355
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oxidation on the Mechanical Response of Isolated Elastin and Aorta

Abstract: Oxidation of aorta by hydroxyl radicals produces structural changes in arterial proteins like elastin and collagen. This in turn results in change in the mechanical response of aorta. In this paper, a thermodynamically consistent constitutive model is developed within the framework of mixture theory, to describe the changes in aorta and isolated elastin with oxidation. The model is then studied under uniaxial extension using experimental data from literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The UPE wavelengths obtained in the present study for elastin and phospholipids were similar to their reported fluorescence emission ranges 34 , 35 . UV-irradiated elastin was previously shown to produce hydrogen peroxide 36 and oxidation was reported to cause structural changes to elastin 37 . The effects of oxidized phospholipids suggest their potential relevance in different pathologies, including atherosclerosis, acute inflammation, lung injury, and many other conditions 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The UPE wavelengths obtained in the present study for elastin and phospholipids were similar to their reported fluorescence emission ranges 34 , 35 . UV-irradiated elastin was previously shown to produce hydrogen peroxide 36 and oxidation was reported to cause structural changes to elastin 37 . The effects of oxidized phospholipids suggest their potential relevance in different pathologies, including atherosclerosis, acute inflammation, lung injury, and many other conditions 38 .…”
Section: Discussionmentioning
confidence: 99%